Interferon-λ3 Promotes Epithelial Defense and Barrier Function Against Cryptosporidium parvum Infection - Ferguson, Sylvia H. (Cell Mol Gastroenterol Hepatol, 2019)
BACKGROUND & AIMS: The epithelial response is critical for intestinal defense against Cryptosporidium, but is poorly understood. To uncover the host strategy for defense against Cryptosporidium, we examined the transcriptional response of intestinal epithelial cells (IECs) to C parvum in experimentally infected piglets by microarray. Up-regulated genes were dominated by targets of interferon (IFN) and IFN-λ3 was up-regulated significantly in infected piglet mucosa. Although IFN-λ has been described as a mediator of epithelial defense against viral pathogens, there is limited knowledge of any role against nonviral pathogens. Accordingly, the aim of the study was to determine the significance of IFN-λ3 to epithelial defense and barrier function during C parvum infection. METHODS: The significance of C parvum–induced IFN-λ3 expression was determined using an immunoneutralization approach in neonatal C57BL/6 mice. The ability of the intestinal epithelium to up-regulate IFN-λ2/3 expression in response to C parvum infection and the influence of IFN-λ2/3 on epithelial defense against C parvum invasion, intracellular development, and loss of barrier function was examined using polarized monolayers of a nontransformed porcine-derived small intestinal epithelial cell line (IPEC-J2). Specifically, changes in barrier function were quantified by measurement of transepithelial electrical resistance and transepithelial flux studies. RESULTS: Immunoneutralization of IFN-λ2/3 in C parvum–infected neonatal mice resulted in a significantly increased parasite burden, fecal shedding, and villus blunting with crypt hyperplasia during peak infection. In vitro, C parvum was sufficient to induce autonomous IFN-λ3 and interferon-stimulated gene 15 expression by IECs. Priming of IECs with recombinant human IFN-λ3 promoted cellular defense against C parvum infection and abrogated C parvum–induced loss of barrier function by decreasing paracellular permeability to sodium. CONCLUSIONS: These studies identify IFN-λ3 as a key epithelial defense mechanism against C parvum infection.